2016
DOI: 10.1051/matecconf/20166600017
|View full text |Cite
|
Sign up to set email alerts
|

Tracking architectural defects in university building in Malaysia

Abstract: Abstract. Building defects are always the key concern in the construction industry. Defects represent not only a loss to the project but also hamper the smooth operation of a building. Recognising the need to resolve these continuing problems, a research was mooted to track from the study of defects that occurred during the Defects Liability Period in a public university in Malaysia. This paper presents part of the research which investigates what can be learnt from the analysis of architectural defects in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Building defects can create hazards leading to serious or fatal injuries. Classification of building defects into categories is useful for identifying the type of defect and to estimate probable causes and its recurrence (Haryati, Kharizam, Zainol & Othman, 2016). Most defects can, at their early stages, be discovered through visible or detectable symptoms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Building defects can create hazards leading to serious or fatal injuries. Classification of building defects into categories is useful for identifying the type of defect and to estimate probable causes and its recurrence (Haryati, Kharizam, Zainol & Othman, 2016). Most defects can, at their early stages, be discovered through visible or detectable symptoms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results highlighted that users were satisfied with the residential environment. Isa et al (2016) identified architectural defects in academic facilities, depicting potentials for future improvements. The study adopted a mixed-method approach, including quantitative and qualitative methods.…”
Section: Literature Reviewmentioning
confidence: 99%